2019
DOI: 10.1101/699900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From reporters to endogenous genes: the impact of the first five codons on translation efficiency in Escherichia coli

Abstract: Translation initiation is a critical step in the regulation of protein synthesis, and it is subjected to different control mechanisms, such as 5' UTR secondary structure and initiation codon context, that can influence the rates at which initiation and consequentially translation occurs. For some genes, translation elongation also affects the protein synthesis rate. Recently, it was proposed that the identity of codons three to five, called short translational ramp, have a strong influence on translation elong… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…However, a recent study by Moreira et al . (2019) supports that these findings are universally applicable. Moreira et al .…”
Section: Coding Sequencesupporting
confidence: 61%
See 1 more Smart Citation
“…However, a recent study by Moreira et al . (2019) supports that these findings are universally applicable. Moreira et al .…”
Section: Coding Sequencesupporting
confidence: 61%
“…It is unclear whether the findings are universally applicable, since Verma et al used only GFP in their study. However, a recent study by Moreira et al (2019) supports that these findings are universally applicable. Moreira et al found that naturally highly abundant native E. coli proteins are enriched with the AA compositions that improved protein production according to Verma et al (2019).…”
Section: Influence Of Amino Acids On Protein Abundancementioning
confidence: 86%
“…Recent investigations on NCS toolbox development have mainly been conducted in prokaryotes, such as E. coli and B. subtilis , where high‐throughput datasets and statistical analysis were applied. [ 3–8,37–40 ] Abundant evidence shows that both N‐terminal fragments from endogenous genes and randomly synthesized NCSs regulate gene translation levels efficiently and effectively. [ 3,4,6,8 ] However, an NCS toolbox for S. cerevisiae has not yet been developed.…”
Section: Discussionmentioning
confidence: 99%
“…4 Interestingly, native E. coli (and Saccharomyces cerevisiae) ORFs are enriched in the high-scoring sequences at codons 3− 5 from the eGFP library. 1 Based on a computational analysis, Moreira et al 5 found that two other enterobacteria (Klebsiella oxytoca and Enterobacter asburiae) are also enriched for highscoring sequences at codons 3−5, indicating a strong positive selection for particular sequences in this region. The idea that codons 3−5 function as key translation success factors is bolstered by another observation: native E. coli ORFs with high eGFP-scoring sequences 1 are associated with slightly higher translation efficiencies and protein abundances as determined from ribosome profiling and proteomic inventory data, respectively.…”
mentioning
confidence: 99%
“…The idea that codons 3−5 function as key translation success factors is bolstered by another observation: native E. coli ORFs with high eGFP-scoring sequences 1 are associated with slightly higher translation efficiencies and protein abundances as determined from ribosome profiling and proteomic inventory data, respectively. 5 Why was a stronger correlation not observed between the codon 3−5 sequences and native protein synthesis rates? Bacterial translation is choreographed by a complex suite of determinants, making it difficult to unmask the exclusive contribution of the N-terminal sequence to systemwide expression of endogenous proteins without fully parsing potential counterbalancing determinants (e.g., mRNA-specific differences in coupling of transcription and translation, variable length of 5′-UTRs 5 ).…”
mentioning
confidence: 99%